EFFECTS OF ASCORBYL PALMITATE AND METAL IONS ON OXIDATION OF SUNFLOWER OIL UNDER ACCELERATED OXIDATION CONDITIONS - A. Baştürk; G. Boran; I. Javidipour (Journal of Animal and Plant Sciences, 2017)
In this study, oxidative stability of sunflower oil was studied under accelerated oxidation conditions. First, refined commercial sunflower oil was examined for its composition of fatty acids and tocopherols. Then, oil samples were prepared with Fe+2 and Cu+2 ions (0, 0.15 and 0.3 mg/kg) and ascorbyl palmitate (0, 200 and 400 mg/kg). Oil samples were kept at different temperatures (30, 50 and 70°C) for 20 days. Oxidation parameters including peroxide value, malonaldehyde concentration and hexanal content were periodically followed during the storage to investigate the effects of metal ions and ascorbyl palmitate on oxidation of sunflower oil. Results showed that temperature had significant effects on elevation of all oxidation parameters studied (P<0.05). It was also found that the concentrations of metal ions and ascorbyl palmitate significantly affected the oxidation of sunflower oil. Addition of 400 mg/kg ascorbyl palmitate restricted increment of peroxide value in both Fe2+and Cu2+ added samples. While Fe2+ significantly increased the hexanal content, the presence of Cu2+ increased both hexanal and malonaldehyde values in sunflower oil during oxidation. In samples held at lower temperatures, the hexanal content was almost steady but dramatically increased at higher temperatures. It is concluded that hexanal content could be well considered as an indicator of oil oxidation along with malonaldehyde concentration.
Keywords: Sunflower oil; hexanal; malonaldehyde; peroxide value; oxidative stability